Low disease awareness as a contributing factor to the high prevalence of hepatitis C infection in Tzukuan, a hyperendemic area of southern Taiwan. Issue 7 (29th April 2022) - Tsai, Pei‐Chien; Dai, Chia‐Yen; Huang, Ching‐I; Yeh, Ming‐Lun; Huang, Chung‐Feng; Hsieh, Meng‐Hsuan; Yang, Jeng‐Fu; Hsu, Po‐Yao; Liang, Po‐Cheng; Lin, Yi‐Hung; Jang, Tyng‐Yuan; Hsieh, Ming‐Yen; et al.
Abstract: Understanding the barriers and tackling the hurdles of hepatitis C virus (HCV) care cascades is key to HCV elimination. The current study aimed to investigate the rates of disease awareness, link‐to‐care, and treatment uptake of HCV in a hyperendemic area in Taiwan. Tzukuan residents from 2000 to 2018 were invited to participate in the questionnaire‐based interviews for HCV. The rates of disease awareness, accessibility, and anti‐HCV therapy were evaluated in anti‐HCV‐seropositive participants. Among 10, 348 residents, 1789 (17.3%) were anti‐HCV seropositive. Of these 1789 anti‐HCV‐seropositive participants, data of 594 participants from questionnaire‐based interviews in 2005–2018 were analyzed for HCV care cascades. Overall, 24.9% of anti‐HCV‐seropositive HCV participants had disease awareness, 53.9% of aware participants had accessibility, and 79.8% of assessed participants had received HCV treatment, with a community effectiveness of 10.7%. HCV prevalence decreased over time, from 21.2% in the early cohort to 9.3% in the recent cohort. Disease awareness increased over time, from 15.6% to 41.7%, with the community effectiveness increasing from 1.3% to 28.8%. Lower education levels and normal liver biochemistry were associated with a lower rate of disease awareness. Notably, 68% of participants with abnormal liver biochemistry and 69% of those with advanced fibrosis (FIB‐4 > 3.25) were unaware of their HCV disease. We demonstrated huge gaps in disease awareness, link‐to‐care, and treatment uptake in the HCV care cascade in an HCV‐hyperendemic area, even in the initial era of direct‐acting antiviral agents. There is an urgent need to overcome these hurdles to achieve HCV elimination.